Reforming the Teaching Hospital’s Organization to Produce More High-Performing Clinical Teachers - Bismantara, Haryo (BKM Public Health and Community Medicine, 2024)
Purpose: To provide perspectives on the clinical teachers’ current situation in the Indonesian teaching hospital, and the needed organizational changes to improve their performances. Content: Clinical teacher is one of the essential customers of teaching hospital in Indonesia. High-performing clinical teachers are required in advancing students’ clinical competence, building supportive learning environment, and driving innovation. The Ministry of Health (MoH) Regulation No. 31/2022 provides several details on clinical teacher management, including the recruitment, registration, tasks, and supervision. However, the details on how the teaching hospital should be shaped to support them is still absent. Currently, several teaching hospital organizations might be counterproductive in achieving high-performing clinical teachers due to several conditions, such as limited high-level leadership support, insufficient technostructure, overemphasis on administrative tasks, insufficient reward system, poor communication, and limited professional development opportunities. Hence, the future policy should consider adding an organizational standard as a mandatory certification criterion for all teaching hospitals. The standards should include: (1) The inclusion of academics in the board of directors (strategic apex), which is a common practice in MoH-owned teaching hospitals, but not in the province/district-owned teaching hospitals; (2) The establishment of a program manager, covering both clinical rotation and residency programs (middle-line), who is a full-time professional with expertise in communication and network coordination under the direct/command line to the board of directors; (3) Strengthening both the Education and Research Coordination Committee (technostructure) with full-time clinical staffs who are paid full-time to lead the committees. Recruiting the retired clinical staff should be the best practice, since the position requires a wise and well-respected person; (4) Improving the support staff with experts in managing clinical teacher’s administrative needs and searching for CPD and research grant opportunities.